International Remittances: A Source of Development Finance – Evidence from North Macedonia - Jovanovski, Kiril; Jusufi, Learta (EBES - Eurasia Business and Economics Society, 2022)
The aim of this study is to provide a general overview of remittances received in North Macedonia, their channels and cost of transmission, their country of origin, their usage, as well as try to elaborate their potential impact in the economy. In North Macedonia private transfers account for around 16% of the GDP per year. It is estimated that at least half of these private transfers are consisted of cash remittances that directly contribute to Macedonian households. Nevertheless, emigration and remittances are not tackled enough in official surveys and policies, leaving no room for proper research in this regard.
Keywords: Remittance, Financial development, Emigration